A Virtual Reality Game-Based Exercise Program to Improve Upper Extremity Function in Children with Cerebral Palsy - Ramadhani, Jihan Nabila; Pristianto, Arif; Perdana, Suryo Saputra (Urecol Journal. Part C: Health Sciences, 2025)
Cerebral palsy (CP) is a neurological disorder that causes motor developmental delays in children, particularly in upper extremity function. The monotony of conventional therapy often leads to children losing motivation to practice regularly. This research developed a Virtual Reality (VR) game-based exercise program designed to be gradual, interactive, and fun to address this issue. Research and Development (R&D) was conducted using an expert adjustment approach. This game is tailored to children's motor and cognitive abilities and includes a progress tracking and evaluation system. This development is expected to result in improved fine and gross motor skills, increased patient engagement during therapy, and the availability of flexible, easy-to-use, and effective therapeutic aids for therapists and parents. This is a new innovation in pediatric physiotherapy that combines technology and motor therapy to achieve more progressive and enjoyable results.